An In-Depth Examination of Diverse Industrial Loads and their Impact on a Solar-Based Microgrid - Niloy Sarker; Md Kabiruzzaman; Md Kabiruzzaman (Global Journals of Research in Engineering, 2022)
Micro grids are expanding and mechanical increases are being introduced, costs decreased, participation seen and advantages recognized in industry sectors, banks and pilot exhibition venues. They are employed to enhance the stability and power of intensity frames, and to cope with increasing renewable, transmitted utilities like the age of wind and sunlight, in places that lack an electrical grid, to mitigate petroleum emissions or electricity. In todays world solar is an important source of renewable energy. In industrial revolution all the countries try to use their existing resource as much efficiently. This paper about the efficient use of solar as a renewable energy and how industrial load behave against the system that proposed. As try to implement maximum power from the photo voltaic cell here use perturb and observe method for constant output.